Meaningful Learning Experiences in Everyday Life During Pandemics. A Qualitative Study - González-Ceballos, Irene; Palma, Montserrat; Serra, Josep Maria; Esteban-Guitart, Moisès (Frontiers in Psychology, 2021)
The Covid-19 pandemic has drastically changed the lives of people all over the world. In particular, an unprecedented educational crisis has occurred due to the circumstances of physical distancing and remote learning. This article focuses specifically on the meaningful learning experiences in the everyday lives of adolescents during the pandemic. 72 meaningful learning experiences were identified from 11 participants who recorded their specific learning experiences for a week by a means of a journal recorded by themselves. A content analysis was undertaken in order to identify the ecology (what, how, where, and who with) of the different learning experiences. The results show a prevalence of personal and conceptual learning, a presence of both formal and specifically informal, everyday activities among the meaningful learning experiences detected, the importance of peers, teacher and “learning experiences while alone”, and the use of digital technologies as learning resources; they also reveal the assistance of others in the learning process. The main contribution of this study illustrates how students in everyday life during pandemics are involved in a whole range of different activities both at school and at home.